Exploring the Relationship Among Preservice Teachers’ E-Learning Readiness, Learning Engagement, and Learning Performance in HyFlex Learning Environments - Ramos, Alvin M.; Lee, Hyunkyung; Mabuan, Romualdo A. (International Review of Research in Open and Distributed Learning, 2025)
This study investigated the relationship among e-learning readiness, learning engagement, and learning performance of preservice teachers in HyFlex learning environments. To identify the causal relationship, data collected from 776 preservice teachers at four universities in the Philippines were analyzed using structural equation modeling (SEM). The results indicated that e-learning readiness and learning engagement are significantly related to students’ perceived learning performance. In addition, e-learning readiness mediates the relationship between learning engagement and learning performance. Given that the educational landscape has been transcending conventional delivery methods and now includes the HyFlex modality, education designers and learning facilitators must create dynamic and holistic learning delivery to enhance students’ e-learning readiness and learning engagement. Moreover, a student’s learning engagement may not be sufficient to predict the learning outcomes solely without the help of e-learning readiness in HyFlex learning environments. Findings shed light on which e-learning readiness construct is paramount for effective HyFlex learning environment design in education.